Design For Monitoring Current And Voltage In Battery Charger Using NodeMCU Esp8266 Microcontroller And The Blynk Appdi Silampari Airport Lubuk Linggau–South Sumatra - Muhammad Caesar Akbar; Mikael Angripa Saragih (Jurnal Info Sains : Informatika dan Sains, 2024)
At Silampari Airport there are frequent power outages not only 1 to 2 times a day and even experienced up to 4 blackouts. During the second blackout on the same day, the 550 kVA generator failed to start due to a voltage drop in the generator battery. This condition could result in disruption of the operational system at Silampari Airport.. Dbecause Silampari airport does not have a spare battery, so the voltage and current values of the battery must be detected, so that the generator does not fail to start. To monitor the battery and to find out the value of the battery input voltage, battery power and remaining battery power, a voltage and current monitoring design for the 550 generator battery charger is required. Kva.Presearch This method uses descriptive analysis and a qualitative approach. The result of this research is that a control system for regulating voltage and load current using NodeMCU ESP8266 based on the Internet of Things with the Bylnk platform has been realized. The design of the tool has been realized as a tool for monitoring battery charger voltage and current using the IoT concept by utilizing the main components, namely the voltage sensor, ACS712 current sensor, NodeMCU data processor equipped with an IoT module in the form of ESP8266.